Corporate disclosures, 1553 to 2007 AD : the origin of financial and business reporting - Jaganathan, Shankar (New Delhi : Routledge, Taylor & Francis Group, 2009)
With partial reference to corporate disclosures in India.
Includes statistics.
Includes bibliographical references and index.
Keywords: Disclosure in accounting -- History; Corporations -- Accounting -- History; Financial statements -- History; Disclosure in accounting -- India; Financial statements -- India